Evidence or Evidence Based Practice? An Analysis of IASL Research Forum Papers, 1998-2009 - Mardis, Marcia A. (Evidence Based Library and Information Practice, 2011)
Objective - Conferences are essential opportunities for professional development and for learning about research. This study analyses papers presented in the Research Forum track of the International Association of School Librarians (IASL) conferences to determine whether the amount of school library research reporting increased or decreased over time; who (i.e., what author roles and affiliations) has written about research; which countries were represented in the research articles; what topics were discussed in research articles; and what research methodologies were used. The aim was to determine the extent to which the Research Forum provides research evidence that relates to practice. Methods - This study continues the longitudinal analysis of published school library research begun by Clyde (1996) by analyzing Research Forum papers published in IASL conference proceedings from 1998-2009 and using the same approaches and metrics as previous studies by Clyde (e.g., 1996; 2002; 2004), Clyde and Oberg (2004), and Oberg (2006). Results - Conference paper topics, author origins, quantities, and research approaches remained static through the 11 years analyzed. The analysis reveals that the papers’ authors, methods, and topics reflected those found in previous studies of school library research. As well as replicating previous studies, the role of academic research at a practitioner-based conference was investigated. Conclusions - Based on long-established imperatives from leaders in the profession, the IASL conferences provide both evidence and evidence -based practice for school librarians from all over the world. However, when scholarly research is shared at practitioner venues, it is possible that school librarians may assume that research results constitute evidence -based practice (EBP), not evidence upon which practice should be based. This distinction is important if considering that the purpose of academic research is to objectively inform, not to advocate a particular position or practice. The Research Forum can be a valuable venue for the presentation of empirical research findings and conclusions and objective program evaluations and provide a valuable complement to the evidence -based practice descriptions shared in the Professional Papers portion of the conference program. It is argued that the Research Forum must be clear in its purpose: to present the results of research; to present effective practice determined by rigorous evaluation; or to present research-supported arguments for the support of school libraries. Through a reconceptualization of EBP, the paper demonstrates how EBP is both a method and a methodology for the presentation of school library research and practice in a conference atmosphere.